2013
DOI: 10.2209/tdcpublication.54.265
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year Activity Report from the Oral Cancer Center, Tokyo Dental College

Abstract: The Tokyo Dental College Oral Cancer Center was established on April 1st, 2006 at our Ichikawa General Hospital for the purpose of providing multimodal treatment for oral cancer. This report summarizes the Center's activities over the last 5 years. The total number of oral cancer patients treated was 360 (April 2006 to March 2011), with 205 primary cases. We investigated the following treatment-related items: 1) site, 2) age, 3) sex, 4) pathological examination, 5) staging, 6) systemic disorder, 7) double canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Considering that cancers of the oral cavity are highly frequent in southern Asia, the higher proportion in young people might indicate that the sociocultural lifestyle of the population, such as betel quid chewing and the use of tobacco and alcohol, plays an important role in this geographic or regional diversity [27]. In our study, the percentage of patients with early stage (Stage I-II, 50.68%) was lower than in western developed countries [20], but higher than other southern Asian regions (e.g., India, Thailand, Taiwan, and Japan) [11,14,17,19,[28][29][30]. It is suggested that low socioeconomic status or related patient factors (e.g., education, diet, health care, and living conditions) may increase the risk of OC-SCC.…”
Section: Discussionmentioning
confidence: 65%
“…Considering that cancers of the oral cavity are highly frequent in southern Asia, the higher proportion in young people might indicate that the sociocultural lifestyle of the population, such as betel quid chewing and the use of tobacco and alcohol, plays an important role in this geographic or regional diversity [27]. In our study, the percentage of patients with early stage (Stage I-II, 50.68%) was lower than in western developed countries [20], but higher than other southern Asian regions (e.g., India, Thailand, Taiwan, and Japan) [11,14,17,19,[28][29][30]. It is suggested that low socioeconomic status or related patient factors (e.g., education, diet, health care, and living conditions) may increase the risk of OC-SCC.…”
Section: Discussionmentioning
confidence: 65%
“…Published studies have demonstrated a decisive role of TNM staging in the prognostic outcome of oral cancer cases (Table 2). [22][23][24][25] Kreppel et al, in 392 oral cancer patients, showed that pTNM had a higher prognostic superiority than cTNM. 26 Other studies have also revealed a significant influence of TNM staging on prognosis and long-term survival.…”
Section: Tnm Stagingmentioning
confidence: 99%
“…Together, oropharyngeal cancer and oral cavity cancer account for 85% of all head and neck cancers [1]. In the oral cavity, the oral portion of the tongue is the most common site, followed by mandibular gingiva, maxillary gingiva, floor of mouth, and buccal mucosa [2]. Cigarette smoking and alcohol consumption are risk factors commonly associated with oral cavity cancers [3,4].…”
Section: Value Of Fdg Pet/ct Stagingmentioning
confidence: 99%